Development of genome-wide SSR markers through in silico mining of guava (Psidium guajava L.) genome for genetic diversity analysis and transferability studies across species and genera - Pramanik, Kritidipta; Goswami, Amit Kumar; Kumar, Chavlesh; Singh, Rakesh; Prabha, Ratna; Jha, Shailendra Kumar; Thakre, Madhubala; Goswami, Suneha; Aditya, Kaustav; Maurya, Avantika; Chanda, Sagnik; Mishra, Prabhanshu; et al. (Frontiers in Plant Science, 2025)
Guava (Psidium guajava L.) is one of the economically major fruit crops, abundant in nutrients and found growing in tropical-subtropical regions around the world. Ensuring sufficient genomic resources is crucial for crop species to enhance breeding efficiency and facilitate molecular breeding. However, genomic resources, especially microsatellite or simple sequence repeat (SSR) markers, are limited in guava. Therefore, novel genome-wide SSR markers were developed by utilizing chromosome assembly (GCA_016432845.1) of the “New Age” cultivar through GMATA, a comprehensive software. The software evaluated about 397.8 million base pairs (Mbp) of the guava genome sequence, where 87,372 SSR loci were utilized to design primers, ultimately creating 75,084 new SSR markers. After in silico analysis, a total of 75 g-SSR markers were chosen to screen 35 guava genotypes, encompassing wild Psidium species and five jamun genotypes. Of the 72 amplified novel g-SSR markers (FHTGSSRs), 53 showed polymorphism, suggesting significant genetic variation among the guava genotypes, including wild species. The 53 polymorphic g-SSR markers had an average of 3.04 alleles per locus for 35 selected guava genotypes. Besides, in this study, the mean values recorded for major allele frequency, gene diversity, observed heterozygosity, and polymorphism information content were 0.73, 0.38, 0.13, and 0.33, respectively. Among the wild Psidium species studied, the transferability of these novel g-SSR loci across different species was found to be 45.83% to 90.28%. Furthermore, 17 novel g-SSR markers were successfully amplified in all the selected Syzygium genotypes, of which only four markers could differentiate between two Syzygium species. A neighbour-joining (N-J) tree was constructed using 53 polymorphic g-SSR markers and classified 35 guava genotypes into four clades and one outlier, emphasizing the genetic uniqueness of wild Psidium species compared to cultivated genotypes. Model-based structure analysis divided the guava genotypes into two distinct genetic groups, a classification that was strongly supported by Principal Coordinate Analysis (PCoA). In addition, the AMOVA and PCoA analyses also indicated substantial genetic diversity among the selected guava genotypes, including wild Psidium species. Hence, the developed novel genome-wide genomic SSRs could enhance the availability of genomic resources and assist in the molecular breeding of guava.